Oriental melon roots metabolites changing response to the pathogen of Fusarium oxysporum f. sp. melonis mediated by Trichoderma harzianum - Li, Chunxia; Nie, Jiahui; Wu, Xingbiao; Zhang, Yuting; Li, Xiang; Wu, Xia; Yin, Kuide; Jin, Yazhong (Frontiers in Sustainable Food Systems, 2024)
Trichoderma SPP. is a recognized bio-control agent that promotes plant growth and enhances resistance against soil-borne diseases, especially Fusarium wilt. The relationship between resistance to melon wilt and changes in soil microbiome structures in rhizosphere with plant metabolites is frequently suggested. However, the exact mechanism remains unclear. This study is to investigate the effects of Trichoderma application on the metabolic pathway of oriental melon roots in response to Fusarium oxysporum f. sp melonis in pot experiment. The experiment consisted of three treatments including water-treated (CK), FOM-inoculated (KW), and Trichoderma-applied (MM) treatments lasted for 25 day. Ultra-performance liquid chromatography-electron spray ionization-mass spectrometry (UPLC-ESI-MS) was used to analyzed the compounds in melon roots. The results shown that Trichoderma harzianum application resulted in a reduction in the severity of oriental melon Fusarium wilt. A total of 416 distinct metabolites categorized into 4 groups, were detected among the 886 metabolites analzed.Additionally, 7differetial metabolites were identified as key compounds being accumulated after inoculation with Fusarium oxysporum f. sp melonis (FOM) and Trichoderma. The mechanism by which Trichoderma enhanced melon's resistance to Fusarium wilt was primarily associated with glycolysis/ gluconeogenesis, phenylpropanoid biosynthesis, flavon and flavonol biosynthesis and biosynthesis of cofactors pathway, comparison with the treatments of CK and MM, KW treatment increased the metabolites of flavon and flavonol biosynthesis, suggesting that oriental melon defended against pathogen infection by increasing the biosynthesis of flavonol in KW treatment, whereas, the application of Trichoderma harzianum decreased infection of pathogen, while also increasing the biosynthesis of glycolysis/ gluconeogenesis and biosynthesis of cofactors related to growth. This study aims to enhance our understanding of how melon respond to FOM infection and the mechanisms by which Trichoderma harzianum treatment improves melon resistance at metabolic level.